Duality theories for boolean algebras with operators - Givant, Steven (Springer Monographs in Mathematics, 2014)
In this new text, Steven Givant-the author of several acclaimed books, including works co-authored with Paul Halmos and Alfred Tarski-develops three theories of duality for Boolean algebras with operators. Givant addresses the two most recognized dualities (one algebraic and the other topological) and introduces a third duality, best understood as a hybrid of the first two. This text will be of interest to graduate students and researchers in the fields of mathematics, computer science, logic, and philosophy who are interested in exploring special or general classes of Boolean algebras with operators. Readers should be familiar with the basic arithmetic and theory of Boolean algebras, as well as the fundamentals of point-set topology.